Escape dynamics in moderately damped Josephson junctions (Review Article) - Massarotti, D.; Longobardi, L.; Galletti, L.; Stornaiuolo, D.; Montemurro, D.; Pepe, G.; Rotoli, G.; Barone, A.; Tafuri, F. (Физика низких температур, 2012)
The Josephson effect is a privileged access to the macroscopic quantum nature of superconductors. We review
some ideas and experimental techniques on macroscopic quantum decay phenomena occurring in Josephson
structures. The attention is mainly addressed to intermediate levels of dissipation which characterize a large
majority of low critical current Josephson devices and are therefore an avoidable consequence of nanotechnology
applied more and more to Josephson devices. Phase diffusion phenomena take over thermal activation in
some temperature ranges also affecting the transition to macroscopic quantum tunneling, enriching the phase diagram
mostly defined by the Josephson energy, the temperature and the level of dissipation.